Huntington Beach Miscellaneous (Antique Maytag, Rose O'Reilly's Home, Pier - Watkins, Howard::::::::: (1989)
Adam Watkins and Robin Watkins pushing over tree stump; Rose O'Reilly's home at 10952 Tonga LN, Huntington Beach